Comparison of Passenger Car Equivalency Values Using Time Headway Method and PKJ 2014 at Transmart Kairagi Four-Way Intersection, Manado City - Gabriella Elmalina Tuda; Lucia I. R. Lefrandt; Semuel Y. R. Rompis (CV. Green Publisher Indonesia, 2026)
The Transmart Kairagi Four-Way Intersection is one of the signalized intersections in Manado City that frequently experiences congestion and long queues during peak hours. The Passenger Car Equivalency (PCE) values used in intersection performance analyses generally refer to PKJI 2014; however, these values may not accurately represent current traffic conditions. This study aims to compare PCE values obtained using the Time Headway method with those specified in PKJI 2014 and to analyze their effects on intersection performance. Traffic surveys were conducted over three days (Saturday, September 6; Monday, September 8; and Tuesday, September 9, 2025) from 06:00 to 18:00 local time. Traffic volume data were classified into Motorcycles (MC), Light Vehicles (LV), and Heavy Vehicles (HV). The highest traffic volume was recorded on Monday between 17:00 and 18:00, reaching 3,413.6 passenger car units (pcu)/hour. The results indicate significant differences between the PCE values derived from the Time Headway method and those provided in PKJI 2014, which influence intersection capacity and degree of saturation calculations. These findings highlight the need to update PCE values based on actual field conditions to support more accurate traffic planning and operational management in Manado City